Análise histomorfométrica e estresse oxidativo do músculo sóleo de ratas wistar ooforectomizadas e submetidas à vibração mecânica - Peretti, Ana Luiza (2018)
During menopause, there is a decrease in the production and secretion of the estrogen hormone, which may act on the pathophysiology of inflammatory and chronic-degenerative diseases, many of which can cause changes in muscle tissue. Seeking to prevent disturbances in these tissues, the use of mechanical vibrations has been increasing, aiming to promote the gain of muscle strength. In this way, the objective was to analyze and compare the effects of the wholy body vibration treatment at different periods in the muscle tissue of oophorectomized Wistar rats, a model that simulates hormonal deprivation. For this, 72 animals were randomized into the Pseudoophorectomy (GP) and Oophorectomy (GO) groups. After 60 postoperative days, the animals were submitted to therapeutic interventions and divided into eight subgroups: animals that did not undergo any treatment and euthanized after four (GP4 and GO4) and eight (GP8 and GO8) weeks and animals treated during the same periods (GPT4, GOT4, GPT8 and GOT8). The treatment consisted of the use of vibratory platform, using 60Hz frequency and duration of 10 minutes, three times a week for four or eight weeks. At the end of the treatments, the animals were euthanized and the soleus muscles were collected and processed. The data were analyzed for normality and analysis of the three-way variance, adopting a significance level of 5%. In the morphological analysis, the oophorectomized groups, especially GO8, presented muscular hypotrophy and the groups that performed the treatment demonstrated larger fibers than those that did not, as well as GOT4 and GOT8 resembled the animals of the pseudo-oophorectomy groups. Regarding the cross-sectional area, GPT4 had values higher than GP4 and GPT8 whereas GO8 was lower than GO4, GP8 and GOT8; for larger and smaller diameters of muscle fibers, animals that did not undergo oophorectomy had higher values than those who underwent the procedure, as well as those who performed the treatment in relation to those who did not. For the number of nuclei/fiber, GP4 and GO4 had higher mean values in relation to GPT4 and GOT4 and, when compared to time, the number was higher in four weeks than in eight. There was no statistical difference between the number of capillary/fiber and the percentage of connective tissue. In relation to oxidative stress, there was an increase in lipoperoxidation in the GO8 and GOT8 groups, with the treatment not being effective in reversing this damage; for the other SOD, CAT and ChE variables there was no significant difference. For groups of only four weeks, GO4 presented a neuromuscular junction area smaller than GP4, but GOT4 matched GPT4. For the larger diameter of the junctions, GO4 also presented different ones than the others, however, the GOT4 animals were larger than GPT4. There was predominance of oxidative fibers in the soleus muscle. To sum up, this work can be attributed to the hormonal deprivation muscular hypotrophy in the oophorectomized groups, mainly in GO8, and the reversion of this process and muscular hypertrophy in the groups that performed the treatment with whole body vibration.